Congenital Partial Intercostal Liver Herniation - Basnet, Bal Mukunda; Kandel, Bishnu Prasad; Chaudhary, Gajendra; Simkhada, Prashant; Gyawali, Sandesh; Koirala, Bibek (Journal of Nepal Health Research Council, 2020)
Congenital intercostal liver herniation is a rare entity. The exact etiology of congenital intercostal liver herniation is unknown. Left sided intercostal herniation is even rarer. We present a case report of an eight-day old female who presented to the emergency department of Kanti Children’s Hospital with tissue mass protruding through a defect in the left side of anterior chest wall since birth. Sonographic and radiological investigation revealed the tissue to be an extension of the part of the left lobe of the liver with decreased vascularity. There were no other congenital anomalies. Laparotomy with thoracotomy with resection of the non-viable herniated part and closure of defect was done. During postoperative period patient developed surgical site infection and wound dehiscence for which daily dressing and later secondary suturing was done.Keywords: Intercostal liver herniation